Language Teaching and Learning with the Blended Learning Methodology: Evaluating a Pilot Experience in Universidad Cooperativa de Colombia - Olaya, María Consuelo; Gualdrón, Esmeralda; Gómez, Luis Fernando; Fernández Umaña, Diana Isabel (Rastros Rostros, 2013)
This article presents a research project conducted during 2012 titled Evaluating the pilot of the Open Lingua program at the Bucaramanga campus, based on the Context, Inputs, Processes and Products (cipp) research model of Stufflebeam and Shinkfield (1987). The aim was to evaluate the Open Lingua program, an institutional project that represents an innovative learning space in the field of languages. The results are organized based on the categories of the evaluative model for each level of the participating population. In the first category, context, results show that the Open Lingua program is in line with local problems and requirements, but also reveal the need for widespread dissemination of the program and its inclusion in academic environments and the methodologies of the learners. In the second category, inputs, results confirm that the Blended Leaning methodology is appropriate and suggests building knowledge in it. At the same time it is noted that there are insufficient bibliographical sources, technological support and integration with academic programs, in terms of interdisciplinarity. In the process category, results reveal the need to improve dissemination, systematization, and performance evaluation of the participants as well as of the program itself. Finally, the products category offers a space to analyze and apply corrective measures and innovations for certifying the Open Lingua program.
Keywords: learning; Blended Learning; context; input; processes; products